Implementation Analysis of Army Polytechnic Research Management for The Armament Development of The Indonesian Army - Arief Cahyo Widodo; Agus Heruanto Hadna; Umi Listyaningsih (Populasi)
Implementing Vocational Higher Education in The Army Polytechnic (Poltekad) has used the Triple Helix approach: universities, the private sector, and the government. In its development, Poltekad contributes to the direction of the development of the Army’s technological innovation field. Based on observations of the results of Poltekad research, it has yet to be utilized optimally in fulfilling Army equipment and weapons. In the last three years, 2020–2022, 163 final research assignments were recorded by Poltekad students, and 40 research by Poltekad lecturers. However, only eight lecturers’ research has become research models with the potential for defense and development in the Army. This study uses a qualitative research method, specifically a case study. The study results show that Poltekad has not been able to play a role as a research university, but is still limited to its function as a vocational education institution in the technology field. The allocation of research funds for Poltekad is still relatively small compared to the benefits of research to support the development of Army Armaments. The research themes of lecturers and students are not entirely following the needs of the development of Indonesian Army weaponry technology. The absence of a Poltekad external monitoring and evaluation team for research programs, limited educational laboratory facilities, and qualified lecturers as researchers in the Poltekad environment are several reasons for optimizing the utilization of Poltekad research results which cannot be carried out downstream in the implementation of production activities carried out by the Defense Industry in Indonesia as is stated in the Poltekad vision. Poltekad, as a Research University, needs to pay attention to elements, such as 1) budgeting, 2) Research Programs, 3) monitoring, and evaluation, 4) researcher competence, 5) facilitation facilities, 6) information and communication systems, and 7) scientific publications. Downstreaming the themes to utilize research results is carried out according to needs and developments.